Respuesta :
x - 3y = -7 this is formula 1
2x = 6y-14 this is formula 2
from formula 1, we can change it to
x = -7 + 3y. this is formula 3
now we know x in terms of y
sub it into formula 2
2(-7+3y) = 6y - 14
-14 + 6y = 6y -14
y=0
sub y = 0 into 3
x = -7 + 3x0
x = -7
so x is -7 and y is 0
2x = 6y-14 this is formula 2
from formula 1, we can change it to
x = -7 + 3y. this is formula 3
now we know x in terms of y
sub it into formula 2
2(-7+3y) = 6y - 14
-14 + 6y = 6y -14
y=0
sub y = 0 into 3
x = -7 + 3x0
x = -7
so x is -7 and y is 0
Good Morning, how are you doing?
Were going to try and solve each system using the elimination method:
x - 3y = -7 (Equation 1)
2x = 6y - 14 (Equation 2)
From Equation 1:
x - 3y = -7
Add 3y to each side of the equation:
x - 3y + 3y = -7 + 3y
Therefore:
x = -7 + 3y
Substitute x = -7 + 3y into Equation 2.
Equation 2:
2x = 6y - 14
2(-7 + 3y) = 6y - 14
-14 + 6y = 6y - 14
Add 14 to each side of the equation. We remain with:
6y = 6y
y = 0
OK, now we continue :)
Substitute y = 0 into Equation 1:
x - 3y = -7
x - 3(0) = -7
x - 0 = -7
Add 0 to each side of the equation:
Therefore:
x = -7
Answer:
x = -7 and
y = 0
I hope this helped. :)
Were going to try and solve each system using the elimination method:
x - 3y = -7 (Equation 1)
2x = 6y - 14 (Equation 2)
From Equation 1:
x - 3y = -7
Add 3y to each side of the equation:
x - 3y + 3y = -7 + 3y
Therefore:
x = -7 + 3y
Substitute x = -7 + 3y into Equation 2.
Equation 2:
2x = 6y - 14
2(-7 + 3y) = 6y - 14
-14 + 6y = 6y - 14
Add 14 to each side of the equation. We remain with:
6y = 6y
y = 0
OK, now we continue :)
Substitute y = 0 into Equation 1:
x - 3y = -7
x - 3(0) = -7
x - 0 = -7
Add 0 to each side of the equation:
Therefore:
x = -7
Answer:
x = -7 and
y = 0
I hope this helped. :)